1997
DOI: 10.1002/hep.510260316
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin retards collagen accumulation in early and advanced biliary fibrosis secondary to complete bile duct obliteration in rats

Abstract: rate hepatic collagen accumulation even in advanced (biliary) Silymarin (SIL), a standardized plant extract containing fibrosis; and 3) PIIINP appears to be a suitable serum marker about 60% polyphenole silibinin, is used as a hepatoprotective to monitor the inhibition of hepatic fibrogenesis in this model agent. Its antifibrotic potential in chronic liver diseases has of biliary fibrosis. (HEPATOLOGY 1997;26:643-649.) not been explored. Therefore, we applied SIL to adult Wistar rats that were subjected to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
126
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(132 citation statements)
references
References 25 publications
1
126
0
5
Order By: Relevance
“…The regulation of cysteine synthesis may subsequently contribute to the antioxidant defense [29] . Silymarin reduced collagen accumulation by 30% in biliary fibrosis induced in rats [30] . A study in humans reported a slight increase in the survival of patients with cirrhotic alcoholism compared with untreated controls [31] .…”
Section: Resultsmentioning
confidence: 89%
“…The regulation of cysteine synthesis may subsequently contribute to the antioxidant defense [29] . Silymarin reduced collagen accumulation by 30% in biliary fibrosis induced in rats [30] . A study in humans reported a slight increase in the survival of patients with cirrhotic alcoholism compared with untreated controls [31] .…”
Section: Resultsmentioning
confidence: 89%
“…A total of 30 male Sprague-Dawley rats (200-250 g) underwent bile duct ligation surgery as described previously [17,18] and were sacrificed after 4 or 6 weeks. The animal study was approved by the Animal Care and Use Committee of Xinhua Hospital, Shanghai, China.…”
Section: Methodsmentioning
confidence: 99%
“…15,16) Various plants used in traditional medicine contain significant amounts of iridoid glucosides. [8][9][10]21,22) Some iridoid and phenylpropanoid compounds have rencently been isolated from Boschniakia rossica and presumed to be responsible for its major pharmacological function.…”
Section: Discussionmentioning
confidence: 99%
“…13) By inhibiting lipid peroxidation, silymarin protects against the hepatic toxicity induced by a wide variety of agents. 14,15) Pharmacological studies have indicated that silymarin was not toxic, even at high doses. 16) To evaluate the hepatoprotective mechanism of BRI, serum tumor necrosis factor-(TNF-), hepatic inducible nitric oxide synthase (iNOS), liver oxidative stress and the antioxidative defense system, as well as cytochrome P450 2E1 (CYP2E1), were determined.…”
mentioning
confidence: 99%